THE EFFECT OF OCCUPATIONAL HEALTH ON EMPLOYEE PERFORMANCE WITH WORK ENVIRONMENT AS A MODERATING VARIABLE - Ni Kadek Suryani (ITB AAS Indonesia Surakarta, 2024)
Abstract Researchers believe that if an employee has good health, it can make the employee work more productively, efficiently, enthusiastically, and of course can have a good impact on the employee's performance. Based on this, this research aims to analyze the influence of occupational health on employee performance. In contrast to a number of other studies, this research adds the Work Environment variable as a moderating variable which is believed to strengthen the influence of the Work Environment variable on the Employee Performance variable. The data used in this research is primary data that researchers obtained from 450 employees of Rumah Makan Pagi Sore spread throughout Indonesia. The data obtained from the research was collected using an online questionnaire method in the form of multiple choice questions with 3 major themes covering Occupational Health, Employee Performance and Work Environment. Of course, this research is quantitative research with an exploratory approach by using previous related research as a foundation for leaping higher to discover new novelties. The result in this article show good occupational health can make employees more productive at work, work results more efficient, and time to achieve work targets more effective, which in the end can influence employee performance. The first researcher's hypothesis and speculation could be proven because the P-Values were below the 0.05 significance level, namely 0.011.. Apart from the first hypothesis, researchers can also prove the second hypothesis if a comfortable, safe and peaceful work environment variable, both physical and non-physical, can increase the influence of occupational health on employee performance. The second statement and hypothesis is proven from the results of the third P-Values table, the second line Path Coefficient which is below the significant level of 0.05, namely 0.000, is more significant than the direct tester's 0.011. Based on this, the first and second hypotheses that researchers believe in this article can be proven and accepted. Keywords: Occupational Health, Employee Performance, Work Environment